PENGARUH PENDAPATAN ASLI DAERAH, DANA PERIMBANGAN DAN BELANJA MODAL TERHADAP KINERJA KEUANGAN PEMERINTAH DAERAH KALIMANTAN BARAT - Rimenda Tiara Sembiring; Ira Grania Mustika; Syarif M. Helmi (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2025)
This study aims to investigate how Local Revenue, Balancing Funds, and Capital Expenditures affect the financial condition of the Regional Government in West Kalimantan from 2022-2024. This study uses a quantitative method with secondary data from the Central Statistics Agency (BPS) which is then analyzed using the Eviews 12A application. The data processed includes 42 samples from 14 Regencies/Cities in West Kalimantan. The research findings show that Local Revenue has a significant positive impact on financial performance, while Balancing Funds have a negative impact on financial performance, indicating a potential decrease in the motivation of local governments to optimize local revenue due to dependence on fund transfers. Meanwhile, Capital Expenditures do not show a significant impact on the financial performance of local governments. This study indicates that optimizing Local Revenue is crucial to strengthening regional financial performance. Excessive dependence on Balancing Funds can actually hinder local government efforts to increase Local Revenue. This finding highlights the need for a balance between receiving transfer funds and increasing Local Revenue. The insignificant influence of Capital Expenditures suggests the need to evaluate the effectiveness of regional investment in driving improvements in financial